PENGARUH REWARD, PUNISHMENT DAN INSENTIF TERHADAP SEMANGAT KERJA (Studi Kasus PT Semarang Garment) - Maria Magdalena Minarsih; Tiara Nove Ria (Majalah Ilmiah Inspiratif, 2021)
The method used in this research is quantitative method. Data collection methods in this study use a questionnare. this study use a population of employees with of a Production Factory I in PT Semarang Garment totaling 3.241 employees, with a sample of 97 employees. The sampling technique is purposive random sampling. The data used are primary data and auxiliary data. Primary data is obtained based on the answers from the respondents to questionnare distributed by researchers to the employees of PT Semarang Garment. Based on the answer to the questionnares distributed by the researchers, the original data were obtained which were then process using the SPSS release 21.0 for windows tool. The result obtained from this study concluded that the variable Reward (X1), Punishment (X2), incentive (X3) and Employee Morale (Y)variabels were declared effective and reliable. as well as multiple linear variables. Data processing regression model result as follows: Y = 2.612 + 0,160X1 + 0,230X2 + 0,168X3 + e. For the t Test it can be seen that the independent variables consisting of Reward, Punishment, and Incentive all have a significant positive effect in the dependent variable, namely Employee Morale. While the F test shows that the significance value of 0,000 is smaller than the significant level of 5% or 0,05 which means that the independent variables of Reward, Punishment and Incentive together have a significant positive effect on the dependent variable namely Employee Morale. And to the Determinationcoefficient test R 2  Test explains that the Reward, Punishment, and Incentive have an effect of 53,3% on Employee Morale. And remaining 46,75% is explained by other variables obsutside the research.Keywords : Reward, Punishment, incentive, employee morale.